Technological and nutritional aspects of dark chocolate with added coffee husk flour - Borges, Marília Viana; Leite, Cristina Xavier dos Santos; Santos, Ingrid Alves; Leão, Danilo Junqueira; Ferrão, Sibelli Passini Barbosa; Santos, Leandro Soares; Lima, Amanda Beatriz Sales de; Wobeto, Carmen; Lannes, Suzana Caetano da Silva; Silva, Marcondes Viana da (Pesquisa Agropecuaria Brasileira, 2024)
The objective of this work was to produce dark chocolates with the addition of coffee husk flour (CHF) and to evaluate the generated effects on their physical, physicochemical, microbiological, textural, and rheological characteristics. Husks of the Pacamara coffee (Coffea arabica) variety, produced under organic management, were used. The samples were previously dried, ground, and sieved at 0.250 mm. Five chocolate formulations were previously standardized at 55% content of cocoa solids (mass and cocoa butter) and at 0.4% soy lecithin. The addition of CHF was tested at the concentrations of 0, 2.5, 5.0, 7.5, and 10%, using a completely randomized design and three replicates. The addition of CHF up to 10% alters the physicochemical, textural, and rheological properties of the chocolate formulations, but without compromising their composition and quality. The tested formulations only differed regarding hardness and cohesiveness, evaluated in the texture profile. The hardness of the chocolate formulations increases as CHF is added.
Keywords: Coffea arabica; by-product; Casson model; color; rotational test; sustainability